(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Introduzione. - 2. La qualificazione “religiosa” dei beni culturali. - 3. La legislazione vigente. - 4. Le pertinenze degli edifici di culto. - 5. Casi pratici di sacrificio dell’interesse religioso. In particolare, il caso della Madonna del parto di Piero della Francesca. - 6. Beni culturali e beni comuni. The protection of religious interest of cultural heritage: reflections between ius conditum and ius condendum ABSTRACT: The current perspective, with regard to cultural heritage of religious interest, needs a legislative adjustment on the new person’s protection request. The exam of many practical cases shows, in this matter, that national and economic interests take precedence over religious interests. The reason for this is that many cultural goods of religious interest belong to the State, which claims his exclusive right to use and administer them. It is important to analyze the different interests of the State and the Church, but it is very difficult to find a balance between them. To solve this problem, we can connect the category of the cultural heritage of religious interest to the category of "common goods". The latter goods protect fundamental rights and consider person as the major user of these goods, without taking into account the public and private owners of them. In fact, the cultural heritage of religious interest affects different constitutional rights of the individual, such as the rights relating to the personality, the right to freedom of religion and the right to freedom of art. It is therefore important to consider the needs of the individual to design a correct protection of the cultural heritage of religious interest.